Meningkatkan Minat Wanita Usia Subur (WUS) untuk melakukan pemeriksaan IVA melalui pemberian Buku Saku - Dini Fitri Damayanti; Dianna Dianna; Taufik Hidayat (Jurnal Pengabdian Ilmu Kesehatan, 2023)
Cervical cancer is caused by HPV or Human Papilloma Virus. There are 32,469 cases per year of cervical cancer in Indonesia, with a mortality rate of 18,279 people. Efforts that can be made to increase WUS's interest in conducting IVA examinations are through health promotion activities about IVA examinations. Health promotion is one of the primary prevention that can be done to prevent cervical cancer. The primary prevention strategy that can be done is by providing health education about cervical cancer. The method chosen is to use a pocket book. Pocket books are educational information media with words that are easy to understand, illustration images that are in accordance with attractive designs so as to make WUS understand and understand material about cervical cancer. Pocket books can be taken home and read independently by WUS, so it will cause WUS interest in conducting IVA examinations.